2014
DOI: 10.1186/2048-7010-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity access: a predictor of overweight and underweight among Kenyan women

Abstract: Objectives: There has been a rise in the number of overweight women across the globe and sub-Saharan Africa has not been spared. Our objective was to describe the performance of household food security as a factor in determining overweight and underweight among Kenyan women of child-bearing age. Design: A cross sectional survey using a structured questionnaire was carried out among 656 households with women of child-bearing age from both rural and urban settings in the Rift Valley, Kenya. Results: Of all house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 37 publications
7
28
2
4
Order By: Relevance
“…The food diversity score was similar to what was found in another study undertaken in Addis Ababa and in Kenya [ 7 , 16 ]. Cereals were the most commonly consumed food groups by the study population, with little consumption of fruits, vegetables, and animal products, which can contribute to malnutrition and higher diseases burdens [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…The food diversity score was similar to what was found in another study undertaken in Addis Ababa and in Kenya [ 7 , 16 ]. Cereals were the most commonly consumed food groups by the study population, with little consumption of fruits, vegetables, and animal products, which can contribute to malnutrition and higher diseases burdens [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…The OR for normal weight increased significantly among food insecure male respondents. However, studies on Western industrialized societies' rates of obesity and food insecurity have indicated that those who experience food insecurity are at an increased risk of being overweight and obese compared to their food secure counterparts, and this has been observed across the board among females [ 11 12 14 26 ], children [ 27 ], and adults [ 10 ]. Korean studies also reported similar findings in which bodyweights of low-income children were positively associated with food insecurity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the difference in HFIAS in Keino et al . () study and this study, we can argue that engagement in both urban agriculture and urban‐based rural agricultural activities is associated with improved food security. A comparison of HFIAS between Kisumu and Thika indicates that Thika's households are more food secure with an HFIAS of 5.2, which is significantly lower than Kisumu's households with an HFIAS of 9.6.…”
Section: Resultsmentioning
confidence: 58%